2019
DOI: 10.1111/tpj.14199
|View full text |Cite
|
Sign up to set email alerts
|

Multiple intramolecular trafficking signals in RESISTANCE TO POWDERY MILDEW 8.2 are engaged in activation of cell death and defense

Abstract: The extrahaustorial membrane (EHM) is a host-derived interfacial membrane encasing the haustorium of powdery mildew fungi. Arabidopsis thaliana RESISTANCE TO POWDERY MILDEW 8.2 (RPW8.2) is specifically targeted to the EHM via two EHM-targeting signals. Here, we demonstrate that proper coordination between the trafficking forces engaged via the EHM-targeting signals and the nuclear localization signals (NLSs), as well as the nuclear export signals (NESs), in RPW8.2 is critical for the activation of cell death a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 53 publications
3
27
0
Order By: Relevance
“…Confocal imaging showed that although YFP signal was mainly detected along the plasma membrane of the epidermal cells, it was also found in intracellular structures (Figure 8A). To further determine the subcellular localization of AtANN8‐YFP, we transiently co‐expressed it with an RFP nuclear marker obtained in a previous investigation (Huang et al, 2014) in leaves of Nicotiana benthamiana . While RFP signal from the nuclear marker was exclusively found in the nucleus, YFP signal from AtANN8‐YFP was seen in the cytoplasm with strong signal visible around the nucleus as a typical ER ring (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Confocal imaging showed that although YFP signal was mainly detected along the plasma membrane of the epidermal cells, it was also found in intracellular structures (Figure 8A). To further determine the subcellular localization of AtANN8‐YFP, we transiently co‐expressed it with an RFP nuclear marker obtained in a previous investigation (Huang et al, 2014) in leaves of Nicotiana benthamiana . While RFP signal from the nuclear marker was exclusively found in the nucleus, YFP signal from AtANN8‐YFP was seen in the cytoplasm with strong signal visible around the nucleus as a typical ER ring (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…H 2 O 2 examination in situ production was performed according to Xiao et al (2003). To examine the accumulation of RPW8.1‐YFP or subcellular localization of AtANN8‐YFP, leaves were examined first under a epi‐fluorescent microscope (Nikon 80i) and then performed images acquisition using a confocal laser scanning microscope (Nikon A1; Nikon Instruments Inc., Chengdu, China) as described in a previous report (Huang et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…WRKY53 (ItfWRK21, − 23, − 35, − 59, − 70 and − 71) is an early factor in drought response, and it regulates stomatal movement and early events of leaf senescence by reducing H 2 O 2 content and promoting starch metabolism in guard cells [46]. WRKY6 (ItfWRK3, − 11, − 65, − 62, − 52.1, − 52.2, − 52.3, − 37.1 and − 37.2) participates in the control of aging and pathogen defence [47]. WRKY33 (ItfWRKY 28.1, − 28.2, − 80, − 83.1 and − 83.2) specifically interacts with W-box and responds to salt, cold and heat stresses [14, 48].…”
Section: Resultsmentioning
confidence: 99%
“…Disruption of the nuclear localization signals (NLS) in CaAP2/ERF064 may be an effective, alternative way to approach this, while the RPW8.2 protein confers broad-spectrum resistance against powdery mildew, and the cytoplasmic localization of RPW8.2 could trigger cell death. In contrast, the RPW8.2 protein localization in the nucleus could result in plant resistance to powdery mildew [43,44].…”
Section: Discussionmentioning
confidence: 99%